PEMIDANAAN TERHADAP OKNUM POLRI YANG MELAKUKAN TINDAK PIDANA ILLEGAL LOGGING - Stevani Phinta Silaban; Alvi Syahrin; Suhaidi Suhaidi; Edy Yunara (USU LAW JOURNAL, 2017)
ABSTRACT Illegal Logging is the act of violation of the law committed by any person or group or legal entities in the field of forestry. The overtrhrow of punishment against the person who did the crime police Illegal Logging should be his punishment in more heavy because according to section 13 of act number 2 of 2002 on State Police of The Republik Indonesia in which one of the tasks of the Police is to enforce the law. By using the methods of normative legal research this research will examine about the overthrow of punishment against the person who did the crime Police Illegal Logging and analyzing how the overthrow of punishment procces in the Labora Sitorus as Polres Raja Ampat members who commit criminal acts of Illegal Logging. The result showed that the overthrow of punishment against the police who did the Illegal Logging in section 78 act No. 41 of 1999 on forestry is said to be given criminal sanctions against any person heavy money unlawful din forestry. The overthrow of punishment against the police whi did the Illegal Logging to him must be given criminal heavy punishment because Labora Sitorus is the Police should not be confused with the penalty of civil society. In accordance with the provisions of book 1 of the Penal Code concerning heavy criminal. Basic consideration fo judges in a Judex Facti da until at the level of the supreme court is getting hard punishment Labora Sitorus into 15 years in prison because he found the wrong aplicationof the law and in consideration of its judges also to heavy the defendant because the defendant is a plurality of the national police.   Keywords : Criminalization, National Police Officers, Criminal Act, Illegal Logging